Effects of Flavonoids and Phenolic Acids on the Inhibition of Adipogenesis in 3T3-L1 Adipocytes - Hsu, Chin-Lin; Yen, Gow-Chin (Journal of agricultural and food chemistry, 2007)
Obesity has become a global epidemic in both developed and developing countries, and it is a significant risk factor for various diseases such as diabetes, cancer, heart disease, and hypertension. In the present study, the effect of naturally occurring antioxidants (flavonoids and phenolic acids) on the inhibition of adipogenesis in 3T3-L1 adipocytes was investigated. The results showed that o-coumaric acid and rutin had the highest inhibition on intracellular triglyceride (61.3 and 83.0%, respectively) among 15 phenolic acids and 6 flavonoids tested. However, the oil red o stained material (OROSM) showed that cell number in 3T3-L1 adipocytes was not influenced by those compounds. For glycerol-3-phosphate dehydrogenase (GPDH) activity, the data indicated that o-coumaric acid and rutin had the highest inhibition on GPDH activity (54.2 and 66.8%, respectively) among the compounds tested. o-Coumaric acid and rutin also inhibited the expression of PPARγ, C/EBPα and leptin and then up-regulated expression of adiponectin at the protein level. Some naturally occurring antioxidants efficiently suppressed adipogenesis in 3T3-L1 adipocytes. These results suggest that o-coumaric acid and rutin targeted for adipocyte functions could be effective in improving the symptoms of metabolic syndrome.